Arterial spin labeling to determine tumor viability in head and neck cancer before and after treatment. Issue 4 (4th November 2013) - Fujima, Noriyuki; Kudo, Kohsuke; Yoshida, Daisuke; Homma, Akihiro; Sakashita, Tomohiro; Tsukahara, Akiko; Tha, Khin Khin; Zaitsu, Yuri; Terae, Satoshi; Shirato, Hiroki
<x xml:space="preserve">Abstract</x> Purpose To evaluate the feasibility of arterial spin‐labeling (ASL) in head and neck cancer for noninvasive measurement of tumor blood flow (TBF), by comparing 1) the TBF change before and after the treatment, and 2) posttreatment TBF and its reduction rate between residual and nonresidual tumors after treatment. Materials and Methods Twenty‐two patients with head and neck cancer were evaluated using ASL on 3.0‐T magnetic resonance imaging (MRI) before and after nonsurgical treatment. A pulsed ASL sequence with Look–Locker readout was used to calculate quantitative TBF. TBF reduction rates between pre‐ and posttreatment values were also calculated. Residual tumors were confirmed when present with either histopathologically or clinical follow‐up. Results Pre‐ and posttreatment mean TBF values were 121.4 ± 27.8 (standard deviation) and 24.9 ± 14.9 mL/100g/min, respectively. Pre‐ and posttreatment TBF differed significantly. Posttreatment TBF was significantly higher in patients with residual tumors (five patients, 46.9 ± 7.1 mL/100g/min) than in those without (17 patients, 18.4 ± 9.2 mL/100g/min). The TBF reduction rate was significantly lower in patients with residual tumors (0.540.55 ± 0.120.12) than in those without (0.85 ± 0.06). Conclusion ASL allows quantitative assessment of TBF in head and neck cancer. ASL may be useful for noninvasive assessment of tumor viability in head and neck cancer. J. Magn. Reson. Imaging 2014;40:920–928. © 2013 Wiley Periodicals, Inc.